The Combined Role of Sucrose with IBA and NAA in Rooting of Date Palm Somatic Embryos cv. Khanaizi (Plant Tissue Culture and Biotechnology, 2010)
The combined role of carbohydrate and auxin is effective in root formation of date palm somatic embryos. The best combination resulted a mean of 2.5 roots per embryo and reached up to ten good and healthy roots when the rooting medium containing 60 g/l sucrose supplemented with NAA was used. 60 g/l sucrose combined with 0.4, 0.6 and 0.8 mg/l of either NAA or IBA gave about 74% root thickness. IBA with a low sucrose concentration of 30 g/l promoted root length, while NAA was found to be superior over IBA, when a high concentration of sucrose of 60 g/l was used which may be due to the effect of NAA is on the main root while IBA on the lateral root. Key words: Auxins, Rooting, Combined effect, Date palm, Somatic embryos D.O.I. 10.3329/ptcb.v19i2.5429 Plant Tissue Cult. & Biotech. 19(2): 127-132, 2009 (December)